2015
DOI: 10.11622/smedj.2015020
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Trendelenburg position and the Valsalva manoeuvre on internal jugular vein diameter and placement in children

Abstract: INTRODUCTIONWe compared the effects of various surgical positions, with and without the Valsalva manoeuvre, on the diameter of the right internal jugular vein (RIJV). METHODSWe recruited 100 American Society of Anesthesiologists physical status class I patients aged 2-12 years. The patients' heart rate, blood pressure, peripheral oxygen saturation and end-tidal CO 2 pressure were monitored. Induction of anaesthesia was done using 1% propofol 10 mg/mL and fentanyl 2 μg/kg, while maintenance was achieved with 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“… 17 It also reduces the risk of air embolism. 1 , 5 , 8 Apart from this, the Valsalva manoeuvre and hepatic compression are used to increase the venous return and IJV diameters. 5 , 9 , 14 We found no studies showing the effect of taking advantage of upper-extremity venous drainage on IJV diameter and cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 It also reduces the risk of air embolism. 1 , 5 , 8 Apart from this, the Valsalva manoeuvre and hepatic compression are used to increase the venous return and IJV diameters. 5 , 9 , 14 We found no studies showing the effect of taking advantage of upper-extremity venous drainage on IJV diameter and cross-sectional area.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of IJV cannulation include carotid puncture, nerve damage, hydrothorax, haemothorax, pseudoaneurysm and arteriovenous fistula. 1 , 2 Internal jugular vein (IJV) cannulation is routinely performed with USG in our clinic.…”
mentioning
confidence: 99%
“…One recent study in children showed that Trendelenburg position and Valsalva maneuver increases IJV diameter significantly. [ 6 ] In another study,[ 7 ] Trendelenburg alone increased IJV cross-sectional area by 96% with simulated venipuncture and 40% without simulated venipuncture. Schreiber et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although observational studies report that Trendelenburg positioning (i.e., head down from supine) increases the right internal jugular vein diameter or cross-sectional area in adult volunteers (Category B2-B evidence), [157][158][159][160][161] findings are equivocal for studies enrolling adult patients (Category B2-E evidence). 158,[162][163][164] Observational studies comparing the Trendelenburg position and supine position in pediatric patients report increased right internal jugular vein diameter or cross-sectional area (Category B2-B evidence), [165][166][167] and one observational study of newborns reported similar findings (Category B2-B evidence). 168 The literature is insufficient to evaluate whether Trendelenburg positioning improves insertion success rates or decreases the risk of mechanical complications.…”
Section: Catheter Maintenancementioning
confidence: 99%